Pengukuran Kesenjangan (Gap) Kualitas Layanan Perpustakaan UK Petra dengan Metode Servqual - Kansil, Alvin; Sutapa, I Nyoman (Jurnal Titra, 2013)
The purpose of the research was to measure gap between perceive and expectation of the library users on quality of PCU Library services (gap 5), gap between library user expectations and library management perceptions (gap 1), gap between library user expectations and library staff perceptions (gap 6), and gap between library management perceptions and library staff perceptions about library user expectations (gap 7). The gap analysis used Servqual method.The research result showed that the most negative value of gap 5 is activity staff offer assistance to library users, with a score of -1,47. The most negative value of gap 1 is conformity Digital Theses collection with library userâs needs (-1,00). The most negative value of gap 6 is the existence of DiVo as a means of information and promotion (-0,15). The most negative value of gap 7 is conformity Digital Theses collection with library userâs needs (-1,19).